Epidemiology of Upper Gastrointestinal Damage Associated with Low-Dose Aspirin - Hsu, Ping-I; Tsai, Tzung-Jiun (Current Pharmaceutical Design, 2015)
Low-dose aspirin, commonly defined as 75-325 mg daily, is widely used for cardiovascular (CV) protection. It reduced the risk of CV events and death in patients with coronary and cerebrovascular diseases and has the advantages of both low cost and long duration of antiplatelet action. However, low-dose aspirin therapy is associated with upper gastrointestinal (GI) side effects, which range from dyspepsia (point prevalence: 31%), gastroduodenal erosions (point prevalence: 60%), endoscopic peptic ulcer (3-month incidence: 7%) to symptomatic or complicated ulcers (annual incidence of upper GI bleeding: 0.6%; relative risk of upper GI bleeding: 2.6). The important factors that increase the risk of low-dose aspirin-related ulcer complications include a history of bleeding peptic ulcer, prior peptic ulcer, age > 70 years, H pylori infection, and concomitant drug therapy with non-steroidal anti-inflammatory drugs, other antiplatelet agents (e.g., clopidogrel) or anticoagulants. The use of enteric-coated or buffered preparations do not reduce the risk of upper GI complications. Assessment of GI risk for patients is a crucial step in preventing complications of antiplatelet agents. Patients with a high GI risk should prevent peptic ulcer or ulcer complications by co-therapy with an antisecretory agent, especially proton pump inhibitors. H pylori eradication is recommended for patients requiring long-term low-dose aspirin therapy who have a prior history of peptic ulcer or GI bleeding.
Keywords: low dose